The Effect of Government Expenditure and Private Sector Investment on the Agricultural Sector: A Comparative Analysis of South Africa and Namibia - Mabunda, Fortune Mfundo; Matlasedi, Nchokwe Tony; Zhanje, Stephen (International Journal of Economics and Financial Issues, 2025)
This study investigated the impact of government expenditure and private investment on the agricultural output of two countries in SACU, namely, South Africa and Namibia. The Autoregressive distribution lag model (ARDL) bounds test and Granger causality tests were applied on secondary data spanning the period 1990-2021 to test for the long run relationship and to ascertain if the Keynesian theory and the Wagner theory hold in the economies of the two countries. The Bounds test revealed a significant long-run influence of government expenditure in agriculture, private investment in agriculture and employment in agriculture in both countries. The ARDL test results showed that government expenditure has a positive influence on agricultural output, thus confirming that the Keynesian theory holds in South Africa while being insignificant in Namibia. Private investment showed a positive influence on agricultural output in both countries, thus confirming both the Keynesian and Wagner theories hold. Employment was found to positively influence agricultural output in South Africa, but was negatively related to output in Namibia. The study recommends that government agricultural sector spending should be increased yearly to reach the 10% threshold that is in line with the Malabo declaration.